A Doctrine at Risk: Content Neutrality in a Post-Reed Landscape. Issue 1 (2nd January 2017) - Minchin, Minch
Abstract : Although the Supreme Court of the United States has deployed the content-neutrality doctrine at least twenty-three times in the last decade, two recent cases — McCullen v. Coakley and Reed v. Town of Gilbert — demonstrate that disagreement among the justices over the meaning of the doctrine is endangering its utility for First Amendment jurisprudence. This article describes the manifestations of this disagreement and suggests that without further clarification about the doctrine's nature, purpose and application, the venerable First Amendment canon may soon either lose practical tenability or disintegrate into constitutional oblivion. Such an outcome, the article suggests, is both ill advised and avoidable. By taking several practical steps, the Supreme Court can go a long way toward preserving the doctrine's usefulness for upholding legitimate government interests and protecting the freedom of expression.